2018
DOI: 10.1101/367656
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ubiquitin-dependent and -independent roles of E3 ligase RIPLET in innate immunity

Abstract: The conventional view posits that E3 ligases function primarily through conjugating ubiquitin (Ub) to their substrate molecules. We report here that RIPLET, an essential E3 ligase in antiviral immunity, promotes the antiviral signaling activity of the viral RNA receptor RIG-I through both Ub-dependent and -independent manners. RIPLET uses its dimeric structure and a bivalent binding mode to preferentially recognize and ubiquitinate RIG-I pre-oligomerized on dsRNA. In addition, RIPLET can cross-bridge RIG-I fil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 59 publications
(63 reference statements)
7
48
0
Order By: Relevance
“…The mechanism of Riplet action appears to be considerably more complex than previously thought. Cadena and colleagues have suggested that a Riplet dimer acts as a coreceptor for RIG‐I, with two Riplet‐PRYSPRY domains cross‐bridging and stabilizing two RIG‐I molecules oligomerized on dsRNA . Consistent with our findings, and those of Shi and colleagues, Cadena et al .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The mechanism of Riplet action appears to be considerably more complex than previously thought. Cadena and colleagues have suggested that a Riplet dimer acts as a coreceptor for RIG‐I, with two Riplet‐PRYSPRY domains cross‐bridging and stabilizing two RIG‐I molecules oligomerized on dsRNA . Consistent with our findings, and those of Shi and colleagues, Cadena et al .…”
Section: Discussionsupporting
confidence: 92%
“…Cadena and colleagues have suggested that a Riplet dimer acts as a coreceptor for RIG‐I, with two Riplet‐PRYSPRY domains cross‐bridging and stabilizing two RIG‐I molecules oligomerized on dsRNA . Consistent with our findings, and those of Shi and colleagues, Cadena et al . also show that deletion of Trim25 has no impact on RIG‐I activity in response to either RNA ligands or infection with SeV.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The notion of different E3 ligases playing critical roles in the activation of RIG-I has recently been challenged with some groups identifying Riplet, and not TRIM25, as the required E3 ligase [126][127][128]. The challenge was raised when Riplet -/-, but not TRIM25 -/-, cell lines failed to induce innate immune signalling upon stimulation [126], although these experiments did not address different time points or other stimulation conditions that may trigger RIG-I activation, or the possibility of functional redundancy. Furthermore, it is unclear why different reports using the same TRIM25 -/-MEF cell lines have yielded different results.…”
Section: Innate Antiviral Signalling Functions Of Trim25: Rig-i-depenmentioning
confidence: 99%
“…Additionally, the authors examined a single TRIM25 -/-HEK293T clone which would not eliminate the possibility of off-target effects as a result of the guide RNA used, especially because two TRIM25 -/-HEK293 clones from another study showed a reduced IFN-I response during SeV infection [114]. Riplet -/mice and cell lines are known to have significant losses in both IFN-I and pro-inflammatory responses to infection [123,126,128]. Riplet is also known to bind and ubiquitinate several Lys residues in the CTD and linker region of RIG-I while TRIM25 only targets Lys residues in the 2CARD domain ( Fig.…”
Section: Innate Antiviral Signalling Functions Of Trim25: Rig-i-depenmentioning
confidence: 99%